Reconceptualizing Legal Entity Structures for Indonesian Commercial Crowdfunding - Koeswidi Astuti, Nanin (IJBLE Scientific Publications Community Inc., 2026)
This study examines the optimal legal entity framework for the sustainable development of commercial crowdfunding in Indonesia, with a focus on Equity Crowdfunding and Securities Crowdfunding. Employing a normative and conceptual legal methodology, it analyzes key regulations issued by the Financial Services Authority and assesses their coherence with the constitutional principle of economic democracy. The study contends that legal entity selection plays a critical role in ensuring legal certainty, accountability, and investor protection within crowdfunding ecosystems. It evaluates the suitability of various legal forms, including limited liability companies, cooperatives, foundations, and partnership structures, in facilitating profit-oriented fundraising while preserving market integrity. The analysis underscores the necessity of a clear regulatory distinction between social and commercial crowdfunding models. The findings demonstrate that optimizing legal entity structures is a strategic imperative to enhance fintech governance, expand MSME and startup access to capital, and advance inclusive growth in Indonesia’s digital economy